Legacy of the VOICES Project: Pausing for, Listening to, and Sharing Patient Narratives - Ryan N. Heine; Gheri Terry; Aditya H. Gaur (Journal of Patient-Centered Research and Reviews)
In today’s information-overloaded and fast-paced world, it is imperative that healthcare providers, including clinical care and research teams, “Pause” for, “Listen” to, and “Share” what their patients and research participants have to say. The VOICES Project at St. Jude Children's Research Hospital offers that opportunity and is creating an everlasting, powerful legacy – one that could meaningfully change the healthcare and clinical research landscape.